Pengaruh Transformasi Digital Dan Fleksibilitas Kerja Terhadap Kinerja Pegawai Pada PT. PLN (Persero) Unit Induk Distribusi Sulselrabar - Ikhsan Amar; Kapriani (Movere Journal, 2026)
This study aims to examine the effects of digital transformation and work flexibility on employee performance at PT PLN (Persero) Unit Induk Distribusi Sulselrabar, both individually and simultaneously. The research employed a quantitative approach using an explanatory research design. The sample consisted of 132 employees selected through probability sampling using the simple random sampling technique. Data were collected through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using IBM SPSS Statistics, including validity testing, reliability testing, multiple linear regression analysis, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and the coefficient of determination (R²). The findings reveal that, partially, digital transformation has a positive and significant effect on employee performance, while work flexibility also has a positive and significant effect on employee performance. Simultaneously, digital transformation and work flexibility jointly exert a positive and significant influence on employee performance at PT PLN (Persero) Unit Induk Distribusi Sulselrabar. These findings indicate that strengthening digital transformation initiatives, supported by effective work flexibility practices, can significantly enhance employee performance and contribute to the achievement of organizational objectives.